Microencapsulation of Chilean Papaya Waste Extract and Its Impact on Physicochemical and Bioactive Properties - Yihajara Fuentes; Claudia Giovagnoli-Vicuña; Mario Faúndez; Ady Giordano (MDPI AG, 2023)
The microencapsulation of bioactive extracts of Chilean papaya waste, including both seeds and skin, was investigated. Papaya waste extract microcapsules utilizing maltodextrin at 10% (MD10), 20% (MD20), and 30% (MD30) (w/v) as the wall material through the freeze-drying process were obtained, and subsequently their physicochemical, antioxidant, and antimicrobial properties were evaluated. The TPC efficiency and yield values achieved were more than 60% for the microencapsulated seed and skin extracts, respectively. The best results for phenolic and antioxidant compounds were found in the microencapsulated seed extract with MD20, with a value of 44.20 ± 3.32 EAG/g DW for total phenols and an antioxidant capacity of 12.0 ± 0.32 mol ET/g DW for the DPPH and 236.3 ± 4.1 mol ET/g DW for the FRAP assay. In addition, the seed and skin samples reduced ROS generation in H2O2-treated Hek293 cells. In terms of antimicrobial activity, values ranging from 7 to 15 mm of inhibitory halos were found, with the maximum value corresponding to the inhibition of S. aureus, for both microencapsulated extracts. Therefore, the successful microencapsulation of the waste bioactive extracts (seed and skin) with the demonstrated antimicrobial and antioxidant properties highlight the bioactivity from Chilean papaya waste resources.